Thermal management improvement of a liquid cooled proton exchange membrane fuel cell through adoption of A1₂O₃ nanofluids as cooling medium / Irnie Azlin Zakaria - Zakaria, Irnie Azlin (2016)
Proton Electrolyte Membrane Fuel Cell (PEMFC) has started to gain global attention nowadays due to the greener aspect of this technology with almost 90 % emission reduction as compared to internal combustion engine. However, in order to improve the thermal performance efficiency of a PEM fuel cell, an excellent thermal management system acquisition is strongly required. This study hybridized nanofluids and PEM fuel cell technologies into cooling medium of PEM fuel cell in order to improve the thermal management. To author's knowledge, experimental study of nanofluids in an electrically active heat transfer device such as PEM fuel cell is almost none. The study focuses on Alumina oxides (A1₂O₃) nanofluids characterization, understanding heat transfer and fluid flow behaviour of A1₂O₃ nanofluids in a single cooling plate and later on establishing thermo electrical and thermo fluid performance of a full-scale PEM fuel cell with the adoption of A1₂O₃ nanofluids as the cooling medium. In this study, AI2O3 nanofluids with volume concentration of 0.1, 0.3 and 0.5 volume % have been dispersed in base fluids of water and two mixtures of water and ethylene glycol (EG), which are 60:40 and 50:50 (W:EG). Critical thermo-physical properties of nanofluids mainly electrical conductivity, viscosity and thermal conductivity were measured. Prandtl number and Thermo-electrical conductivity (TEC) ratio were established. These properties were applied to both numerical and experimental study in order to understand the behaviour of A1₂O₃ nanofluids in term of heat transfer enhancement and pressure drop penalty in a single cooling plate of PEM fuel cell. Advantage ratio (AR) was calculated which measure the feasibility of the adoption from heat transfer enhancement to pressure drop penalty aspect. Finally, thermo electrical and thermo fluid effect of A1₂O₃ nanofluids in a full-scale liquid cooled PEM fuel cell was established. The result shows that the highest cooling rate improvement was 187 % with 0.5 volume % concentration of A1₂O₃ nanofluids in 100:0 (W:EG). This was followed with 147 % enhancement in 0.3 volume % concentration of A1₂O₃ nanofluids in 100:0 (W:EG). However, there was a drop in electrical power produced, which is 31 and 15 % respectively as compared to water-cooled PEM fuel cell. Thermo electrical (TE) ratio calculated shows that 0.1 volume % of A1₂O₃ nanofluids in 100:0 (W:EG) are the most feasible A1₂O₃ nanofluids for PEM fuel cell adoption. Thermo fluids analysis through AR was found in a good agreement with TE ratio findings. It was concluded that despite of the high electrical conductivity characteristic of A1₂O₃ nanofluids, the thermal management improvement was still achievable as compared to conventional coolant. It is recommended that further study conducted with different nanoparticles and base fluids to extend the understanding of the nanofluids adoption in an electrically active heat transfer device such as fuel cell.